Merdeka Belajar: Memahami Konsep Pembelajaran Masa Kini - Kamila, Qurota A'yun Ning; ASBARI, MASDUKI; DARMAYANTI, EULIS; Nuraida (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to understand how the Merdeka curriculum shapes contemporary learners. This study's report utilizes a qualitative descriptive method, employing a listening-and-note-taking approach to gather data from the oral narration on the YouTube channel